The Importance of Novelistic Wisdom in Milan Kundera's Critical System - Zaheer Abbas (بازیافت, 2025)
Milan Kundera is undoubtedly one of the greatest intellectuals of the modern era. His status as a novelist is undeniable, but his second greatness is that he has written openly in his articles and interviews about the evaluation of the novel and its distinction from other disciplines.He has proven, through detailed and credible logical reasoning, that the novel is superior to all other academic disciplines in its identification and exploration of human existence.He distinguishes novel,s wisdom from non-novel wisdom in an argumentative manner. In this article, we have tried to examine his thoughts on what grounds he reaches the conclusion that what is novel,s wisdom.In this article, with the help of Kundera's critical approach, we have tried to reach a conclusion on what basis a novel becomes a high novel and for what reasons it falls from the level of a true novel and falls into the realm of a fake novel.